2005
DOI: 10.1038/sj.bmt.1704992
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of WT1 transcripts in bone marrow harvests are associated with a high relapse risk in patients autografted for acute myeloid leukaemia

Abstract: Summary:Relapse postautograft in acute myeloid leukaemia (AML), may in part arise from leukaemia cells present in the bone marrow (BM) inoculum, and the level of minimal residual disease (MRD) in BM harvests used for autografting may therefore be clinically important.We have used the WT1 transcript as a marker of MRD, which was quantitated by RQ-PCR, in the BM harvests of 24 patients receiving an ABMT for AML. ABL was used as a control gene with WT1 level being normalised to 10 5 copies of ABL per sample. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…[1][2][3][4][5]11,12 WT1 expression was most frequently quantified by qRT-PCR applying TaqMan chemistry with various methodologies. However, a uniform approach proven to be reproducible, accurate and comparable on a multicenter basis is currently unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5]11,12 WT1 expression was most frequently quantified by qRT-PCR applying TaqMan chemistry with various methodologies. However, a uniform approach proven to be reproducible, accurate and comparable on a multicenter basis is currently unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…8 WT1 expression has been evaluated as a marker for risk stratification and MRD detection in AML. [1][2][3][4][5][11][12][13][14] However, contradictory reports refer to the value of WT1 hyperexpression for monitoring MRD during front-line chemotherapy and after allogeneic stem-cell transplantation. Although many authors describe a strong predictive value, 3,4,9,10,15 these findings could not be confirmed by others.…”
Section: Introductionmentioning
confidence: 99%
“…50,51 In contrast, the prognostic role of pre-HCT MRD in non-APL AML is primarily studied via MFC-based assays to detect and quantify MRD. 46,47,[52][53][54][55][56][57][58][59][60][61] Nevertheless, as summarized in Table 4, more recent series show that both pediatric and adult patients with non-APL AML who are MRD À by current sensitive methods have excellent outcomes following myeloablative AlloHCT, with 2-5 year OS estimates around 75-80%. 47,58,61 For such patients, even AutoHCT may result in good disease control, with some studies showing 5-year OS estimates in the 60-70% range.…”
Section: The Concept and Determination Of Mrdmentioning
confidence: 99%
“…WT1 expression has already been shown to be a helpful marker in patients with AML after chemotherapy, 19,[21][22][23] after autologous 24 and after conventional allogeneic HCT. [25][26][27] In this analysis, the ability of different markers to predict relapse following allogeneic HCT with RIC was analyzed both alone and in combination.…”
Section: Introductionmentioning
confidence: 99%